A Sharp Decline in Nitrogen Input in a N‐Saturated Subtropical Forest Causes an Instantaneous Reduction in Nitrogen Leaching. Issue 10 (22nd October 2018) - Xie, Danni; Zhang, Ting; Yu, Qian; Huang, Yongmei; Mulder, Jan; Duan, Lei
Abstract: In China, as in other parts of the world, the emission and deposition of reactive nitrogen (N) have been reduced in recent years. Several decades of elevated N deposition in southwest China (40 to 60 kg ha −1 year −1 ) have resulted in extreme cases of N saturation, where N outputs are nearly equal to N inputs. Doubling N inputs using either NH4 NO3 or NaNO3 fertilizer in a subtropical forest in Tieshanping, near Chongqing city in southwest China, caused an immediate doubling of N leaching (as NO3 − ). Reducing N inputs to ambient atmospheric deposition levels after 10 years of fertilization led to a rapid decrease in soil water NO3 − concentration to levels similar to those in the reference plots that had not receive N fertilizer application. NO3 − leaching via the soil water in the NH4 NO3 plots was even lower than that in the NaNO3 plots or the reference plots, confirming the finding of a previous N‐fertilizing experiment that found that NH4 + deposition, in contrast to NO3 − deposition, increased N retention in the forest ecosystem. The N sink remained for at least 2 years after the cessation of N addition. Even with reduced N inputs, ambient atmospheric N deposition caused significant acidification, buffered partly by SO4 2− sorption. Therefore, further abatement of reactive N emissions is necessary in the future. Key Points: Soil nitrogen leaching responded very rapidly to reducing nitrogen deposition in a nitrogen‐saturated forest Soil nitrogen leaching decreased faster with historically high ammonia deposition than nitrate deposition with the same nitrogen level Even with reduced N input, the ambient atmospheric N deposition still caused significant acidification at the study site